DEVELOPMENT TRENDS OF PUBLIC POLICY EXCEPTION IN ARMENIA. AN OVERVIEW IN THE CONTEXT OF POST-SOVIET COUNTRIES - Gharibyan, Davit (State and Law, 2025)
The public policy exception is one of the most important mechanisms of Private International Law that limits the application of the rules of foreign law which are chosen on the basis of conflict of laws principles, if such application may be contrary to the fundamentals of the legal order (public policy) of the Republic of Armenia. It is preferable to study the development tendencies of this mechanism, especially in the context of the Post-Soviet Countries, since its development in Armenia as a general legal concept actually began in the 1960s, when the reforms of the civil legislation of the USSR and Soviet States had launched. Hence, within the framework of this work, a legal comparative analysis of the legislation of Armenia and the majority of Post-Soviet Countries is conducted, judicial practice is discussed and on the basis of mentioned directions for the development of the public policy clause in Armenia are determined.